Prognostic significance of preoperative haemoglobin A1c level in patients with lung adenocarcinoma. (11th June 2021) - Ogawa, Hiroyuki; Fujibayashi, Yusuke; Nishikubo, Megumi; Nishioka, Yuki; Tane, Shinya; Kitamura, Yoshitaka; Nishio, Wataru
Abstract: OBJECTIVES: We investigated the influence of the preoperative haemoglobin A1c (HbA1c) value on the prognosis and pathology of patients with lung adenocarcinoma who underwent surgery. METHODS: We reviewed the medical records of 400 lung adenocarcinoma patients who underwent lobectomy with mediastinal lymph node dissection between 2009 and 2013 using a prospectively maintained database. We stratified 400 patients into 4 groups according to the preoperative HbA1c value as follows: HbA1c ≤ 5.9 ( n  = 296), 6.0 ≤ HbA1c ≤ 6.9 ( n  = 70), 7.0 ≤ HbA1c ≤ 7.9 ( n  = 21) and HbA1c ≥ 8.0 ( n  = 12). We compared the recurrence-free survival and overall survival (OS) among these 4 groups. Univariate and multivariate analyses were performed to identify the risk factors for recurrence. RESULTS: The median follow-up period was 61.2 months. On comparing the recurrence-free survival and OS rates among these 4 groups, we found that these rates among patients in the HbA1c ≥ 8.0 group were significantly poorer compared with the other 3 groups (5-year recurrence-free survival: HbA1c ≤ 5.9, 70.4%; 6.0 ≤ HbA1c ≤ 6.9, 69.7%; 7.0 ≤ HbA1c ≤ 7.9, 70.7%; ≥8.0 HbA1c, 18.8%; P  = 0.002; and 5-year OS: HbA1c ≤ 5.9, 88.7%; 6.0 ≤ HbA1c ≤ 6.9, 80.6%; 7.0 ≤ HbA1c ≤ 7.9, 90.2%; ≥8.0 HbA1c, 66.7%; P  = 0.046). Patients in the HbA1c ≥ 8.0 group had significantly more tumours with vascular invasion ( P  = 0.041) and experienced distant metastasis significantly more often ( P  = 0.028) than those with other values. A multivariate analysis revealed that preoperative HbA1c ≥ 8.0 [hazard ratio (HR) 2.33; P  = 0.026] and lymph node metastasis (HR 3.94; P  < 0.001) were significant independent prognostic factors for recurrence. CONCLUSIONS: Our results revealed that preoperative HbA1c ≥ 8.0 is associated to poor prognosis due to the occurrence of distant metastasis and we should carefully follow these patients after surgery. Clinical registration number: Hyogo Cancer Center, G-57. Abstract : Lung cancer is a major cause of cancer-related death worldwide [1].